Integrasi Mata Pelajaran Fiqih Pada Materi Makanan Minuman Halal Dan Haram Melalui Aplikasi Wordwall Dengan Model Pembelajaran Problem Based Learning Untuk Meningkatakan Kesadaran Siswa Kelas VIII D SMP Wahid Hasyim Sumberwudi Karanggeneng Lamongan - Nadhif, Muhammad; Sholikhah, Khotimatus (Fakultas Agama Islam, 2026)
With the development of the modern era, numerous changes have occurred, including in the food sector. Advances in science and technology have resulted in a wide variety of foods and beverages available in Indonesia, ranging from fast food and instant drinks, local to international. This is undoubtedly a concern for parents and teachers of Wahid Hasyim Middle School students. The purpose of this study was to determine how to increase student awareness of the importance of understanding halal and haram food and beverages through a word wall application using a problem-based learning model. It also explained the importance of raising awareness of halal and haram food and beverage consumption among grade VIII D students of Wahid Hasyim Junior High School. This study employed qualitative methods, utilizing observation, interviews, and documentation as data collection techniques. Furthermore, the researchers employed data analysis techniques, including data reduction, data presentation, and conclusions. From the results of this study, it can be seen that the way to increase students' awareness of the importance of understanding the material on halal and haram food and drinks is by integrating Islamic jurisprudence subjects into the material on halal and haram food and drinks through the wordwall application with a problem-based learning model. so that students are able to understand the material in depth and can increase awareness of the importance of understanding the material on halal and haram food and drinks.